Role of CO2 Laser & Microdebrider in the treatment of Juvenile onset recurrent respiratory papillomatosis - Muhammad Rashid; Humaira Saleem; Muhammad Noman Karim; Atif Najam; Ameer Abdullah; Jawad Haneef (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the efficacy of two main treatment modalities of microdebrider and carbon dioxide laser excision for juvenile onset recurrent respiratory papillomatosis. Method: The retrospective study was conducted in May 2021 at the Combined Military Hospital, Kharian, Pakistan, and comprised data from July 1, 2007, to January 31, 2020, of patients of either gender aged 2-12 years who were treated for juvenile onset recurrent respiratory papillomatosis either with microdebrider excision in group A or carbon dioxide laser excision in group B. Extent and severity of disease was documented as per the Derkay-Coltrera grading system. Data was analysed using SPSS 20. Results: Of the 39 patients, 23(59%) were girls and 16(41%) were boys. The overall mean age at the time of procedure was 6.62±2.06 years. Group A had 22(56.4%) subjects; 15(68.2%) girls and 7(31.8%) boys, while group B had 17(43.6%) cases; 8(47%) girls and 9(53%) boys. The mean operative time for group A was 40.91±11.50 minutes and for group B it was 60.59±19.51 minutes. Postoperative breathing and oedema status was better for group A (p<0.05), while there was no significant difference regarding postoperative pain, residual disease and repeat surgeries (p>0.05). Conclusion: Microdebrider was found to be superior to carbon dioxide laser excision in the treatment of juvenile onset recurrent respiratory papillomatosis. Key Words: CO2 laser, Human papilloma virus, Laryngeal papillomatosis, Recurrent respiratory papillomatosis.